Prognostic relevance of serum β2 microglobulin in patients with follicular lymphoma treated with anthracycline-containing regimens. A GISL study - Massimo Federico; Cesare Guglielmi; Stefano Luminari; Caterina Mammi; Luigi Marcheselli; Umberto Gianelli; Antonino Maiorana; Francesco Merli; Monica Bellei; Samantha Pozzi; Caterina Stelitano; Antonio Lazzaro; et al. (Haematologica, 2007)
Background and Objectives Although serum β2 microglobulin (β2 M) is an easy parameter to measure, and over-expressed in a large number of lymphoproliferative diseases, its prognostic value has been largely underestimated. The present study examined the influence of β2M levels on overall survival (OS) of patients with follicular lymphoma (FL).Design and Methods The prognostic role of β2M was evaluated in 236 patients with FL identified from the databases of the Gruppo Italiano per lo Studio dei Linfomi (GISL) and treated with anthracycline-based regimens from 1993 to 2003.Results Elevated serum β2M levels were found in 82 patients (35%). According to multivariate logistic regression analysis, elevated β2M levels were associated with elevated lactate dehydrogenase (LDH) (p=0.021), age (p=0.029), and number of involved nodal areas (p<0.001). The percentage of elevated β2M levels increased progressively with increasing FLIPI scores (17%, 38%, and 63% in the low-, intermediate-, and high-risk groups, respectively). Five-year OS was 61% (95% CI, 47–73%) and 89% (95% CI, 82–93%) for patients with elevated vs normal β2M levels respectively (p<0.001). Cox regression analysis showed that β2M level had an independent and stable prognostic value (HR=3.0; 95%CI, 1.6–5.7). In a multivariate analysis the impact of β2M level on survival was independent of FLIPI score, with a HR of 2.94 (95% CI, 1.54–5.62).Interpretation and Conclusions Our results demonstrate that in patients treated in the pre-rituximabera, β2M level was an independent prognostic marker in addition to FLIPI score. We thus suggest that β2M be routinely assessed and tested in future prognostic studies of FL patients treated with combination chemotherapy and anti-CD20 agents.